Adhering to a Policy: The Moon Jae-in Government’s Housing Policy in South Korea - Heo, Inhye (Animo Repository, 2024)
In a democratic country, it is not easy for a government to adhere to a public policy when public criticism of its effectiveness is mounted. However, the Moon Jae-in government in South Korea formulated a housing policy based on its ideological goal of pursuing “substantive equality” and adhered to such policy despite the ensuing social discontent. Because policy autonomy is a prerequisite for a government to stick to a policy, this paper aims to analyze this case, focusing on the relationship between the policy autonomy that the Moon government possessed and its adherence to said policy. It presents a theoretical framework that shows the political factors that affect policy autonomy, analyses the Moon government’s housing policy based on its ideological goal, and examines relationships related to the government’s adherence to the policy and the factors discussed in the framework. Based on the research findings, the paper concludes with the theoretical and practical implications of the study.